A Case of Paradoxical Reactions to Biologic Therapy for Psoriasis - Zhou Q; Zhou S; Xiong H; Yang J; Yang Z; Zhou N; Mao J; Li M (Dove Medical Press, 2023)
Qianqian Zhou,1 Shengru Zhou,1 Huizi Xiong,1 Jianqiu Yang,1 Ziliang Yang,2 Naihui Zhou,2 Jinzhu Mao,2 Min Li1,2 1Department of Dermatology, Dushu Lake Hospital Affiliated to Soochow University (Medical Center of Soochow University, Suzhou Dushu Lake Hospital), Suzhou, People's Republic of China; 2Department of Dermatology, The First Affiliated Hospital of Soochow University, Suzhou, People's Republic of ChinaCorrespondence: Min Li, Department of Dermatology, Dushu Lake Hospital Affiliated to Soochow University (Medical Center of Soochow University, Suzhou Dushu Lake Hospital), No. 9, Chongwen Road, Suzhou, 215123, People's Republic of China, Tel +86-18936140383, Email lm@suda.edu.cnIntroduction: Psoriasis is an immune-mediated chronic inflammatory skin disease. As our understanding of the pathogenesis of psoriasis has improved, biologic agents have become increasingly important in the treatment of psoriasis. However, the use of biologic agents is associated with cutaneous side effects. A new type of side effect called paradoxical reactions is an emerging threat arising from the increasing use of biologic agents.Case: Here, we present a case of paradoxical skin reactions - pyoderma gangrenosum (PG) and eczema - induced by biologic therapy. The case was successfully and eventually treated with baricitinib.Discussion: PG is a rare inflammatory disease characterised by painful and necrotic ulcerations containing neutrophils. It has been associated with autoimmune diseases such as inflammatory bowel disease (IBD). TNF (tumor necrosis factor) -α inhibitors can effectively treat refractory PG, while IL (interleukin) − 17A inhibitors may worsen IBD symptoms. The cause of PG in this case was believed to be secukinumab, not adalimumab. The patient was diagnosed with eczematous dermatitis due to TNF-α inhibitors, and baricitinib was added to treat eczematous dermatitis.Conclusion: Paradoxical reactions are unpredictable events that may occur during treatment with biologics at anytime. They need further research in order to formulate personalised treatment.Keywords: biology drugs, pyoderma gangrenosum, eczema, adalimumab, secukinumab, baricitinib